INFORMAL SOCIAL NETWORKS IN A COMMUNITY DAILY LIFE OF FORTALEZA OUTSKIRTS - Fátima Luna Pinheiro Landim; Juliana de Lima Comaru; Rafael Barreto de Mesquita; Patrícia Moreira Collares (Universidade Federal do Paraná, 2006)
The social support networks are not necessarily structured as beneficial systems, they can also represent harmful networks too. This is a descriptive article which aims to describe the building and contextual process of the informal social networks in a community and the ways these networks can evolve as beneficial or harmful. It was carried out from April 2003 to March 2004. The informants were 12 family representatives and the data collection was held through participant observation and interview, the analyses occurring altogether. It has been evidenced two kinds of informal social networks: the communitarian leaders' network as example of beneficial network, and the teen gangs' network, as harmful network. The leaders' network assumes many social roles, from straightening out families' misunderstandings to coping with problems concerning the community survival. On the other end, the gangs' network stand out mainly by their self-destructive potential.